Associations of skin and gut microbiota with vitiligo - WEI Tianqi; XU Beilei; LI Chengrang (Pifu-xingbing zhenliaoxue zazhi)
Vitiligo is characterized by skin depigmentation, with complex pathogenesis and difficult treatment. Recently, more and more studies have shown a correlation between vitiligo and microbiota. This article reviews the changes in microbiota diversity in patients with vitiligo at the progressive and stable stages, as well as the effects of NB-UVB and other treatments on the microbiota in patients with vitiligo. It also summarizes the role and potential pathways of skin and gut microbiota imbalance in the pathogenesis of vitiligo.